Assessing Cardiovascular Fitness on Military Recruitment - Koswara, Jonathan; Yap, Irianto; Chandra, Ricky Alexander; Suwanto, Denny (Universitas Airlangga, 2025)
Background: Military recruitment demands optimal health, with cardiovascular fitness being a key criterion. To assess candidates, military organizations worldwide employ standardized screening protocols. Initial evaluations typically involve history-taking and physical examinations based on guidelines from the American Heart Association and the European Society of Cardiology. Method: Electrocardiography (ECG) serves as an accessible and cost-effective screening tool. Abnormal findings in these initial tests necessitate further assessments to determine a candidate’s fitness for service. Depending on the severity and context, additional tests such as echocardiography or, in rare cases, coronary angiography may be conducted. However, cost constraints influence the extent of these evaluations in some countries. Aim: This article examines cardiovascular screening in military recruitment and the variations in assessment practices across different nations. – Highlights: 1. This article addresses the importance of standardized yet flexible cardiovascular assessments essential for military screenings. While standardized protocols are essential for consistency, military screenings should also adapt to environmental factors, individual differences, and evolving fitness benchmarks to ensure accurate evaluations.